Propagación clonal in vitro y enraizamiento de estacas de algodón nativo (gossypium barbadense l.) (2013)
In order to develop a system of vegetative propagation for Gossypium barbadense, woody species used in textiles and medicine in the ancient pre-Columbian cultures of Peru, was studied in vitro clonal propagation and rooting of cuttings. In in vitro clonal propagation, was evaluated the effect of several growth regulators on the elongation and rooting of shoots and nodal segments. In the rooting of cuttings was valuated the effect of tap water, Knop and Knudson solutions ith growth regulators IAA, IBA and phloroglucinol on uttings obtained from the apical, middle and basal region. In the combination NAA 0.1 mg/L, BAP (1.0 and 2.0 mg/L), after 30 days of in vitro culture, shoots reached 38.1 and 30.7 mm of elongation, with 4.1 and 3.4 nodes formed; the rooting was observed with IAA 0.2 mg/L reached 3.6 roots formed. Cuttings of the middle and upper thirds of the plant, with sprouting of 40 and 50%, showed higher rooting in both tap water and Knop solution supplemented with only IBA 25 and 50 mg/L.